Pengelolaan Bendung Manganti Sebagai Aset Berharga Pendukung Upaya Ketahanan Pangan Nasional - Elroy Koyari; Soni Senjaya Efendi; Martha Nugraha (Akselerasi : Jurnal Ilmiah Teknik Sipil, 2024)
Maintaining infrastructure such as bridges, tunnels, embankments, irrigation systems, and so on needs to be done carefully and thoughtfully, taking into account the relationship between technological and cultural aspects. Taking into account the one potential drawback of the modified infrastructure is the potentially suboptimal return on investment. In order to ensure that both can work together effectively, there are a few steps that need to be taken by the infrastructure development team, such as assessing the human resources involved in the infrastructure development, forming a committee to support the infrastructure development work, securing support from local government agencies and disaster relief units, and encouraging and educating the public about the importance of infrastructure development in a way that is environmentally conscious.Balai Besar Wilayah Sungai (BBWS) Citanduy, and water resources infrastructure management assets in the Citanduy River basin, have carried out operational, maintenance, maintenance, and safety activities for the assets that has become a blind spot; the only aset that has been developed thus far is the bendung manganti. The wetlands in the provinces of West Java and Central Java will be investigated in order to provide more effective land management through the application of information technology and knowledge that can provide faster, more accurate, and more efficient land management.From the social side, in the manganti dam, improvements still have to be made in its management so that it can keep pace with the technical progress that continues to be developed by the head of the hall and his staff. The use of the weir location as a location for crowding of thousands of people during holidays is one example of conditions that must be addressed because it can cause the weir load to increase very high which can interfere with operating performance, hinder proper maintenance and security. One possibility that should be worried is the increasingly severe occurrence of cracks in the bridge floor with a width of up to 0.3 mm and the girder experiencing serious corrosion due to maximum loading which can result in casualties from visitors who are on the bridge. If this incident occurs, the manager and owner of the weir are at risk of disaster that occurs.The methodology used in writing this paper includes conducting social surveys of visitors and managers of the manganti weir during the holiday season, analyzing existing data, concluding the results of the analysis that has been done and proposed improvements in better management of the manganti weir as valuable assets that must continue to be maintained and maintained. Keyword : Water infrastructure, technical, socio-cultural, human resources, weir manganti, science, information technology